Polisse [videorecording (DVD)] - Attal, Alain; Viard, Karin; Joeystarr, 1967-; Foïs, Marina, 1970-; Duvauchelle, Nicolas; Maïwenn, 1976- (Sundance Selects, 2012)
Based on real child investigation cases, Polisse follows the lives of a tight-knit team of men and women working in the Child Protection Unit of the Parisian police. In the realm of some of society's worst criminals, the pressures of the job are matched only by the pressures in the personal lives of the officers. Only by putting aside their individual differences can they find the strength necessary to make a positive change in the community.